PELATIHAN DAN PENDAMPINGAN PENYUSUNAN BORANG AKREDITASI SD YPK SOTA - Fredy Fredy; Mohamad Ilham; Ratna Purwanty; Dewi Puji Rahayu (LPPM Universitas Flores, 2021)
SD YPK Sota, located in the village of Sota, on the RI-PNG border, has long ended its accreditation period. The last accreditation was in 2012 with a C rating. In fact, the eight components of the national education standard have been implemented by partner schools but the documents and activity reports are not well-administered. The results of interviews with partner school principals obtained the same problem, namely the low value of each SNP component referring to the accreditation instrument. Training programs and assistance for the preparation of accreditation forms by the community service team are the solutions offered to help partner school problems. The stages of this community service program include: 1) the training stage, 2) the assistance stage for the preparation of accreditation forms, 3) the assistance stage for the fulfillment of accreditation physical documents, 4) the evaluation stage. The training in the form of providing material on the role of accreditation for the fulfillment of SNP, accreditation tools and accreditation assessment instruments was able to provide understanding to the form drafting team about the importance of school accreditation as a form of school / madrasah accountability to the public and an understanding of the procedures for drafting forms referring to Permendikbud No. 2. In 2017, the focus of the form preparation team is to fulfill every element of the assessment in the assessment instrument. Training in the fulfillment of physical documents and supporting documents provides understanding and skills to the form drafting team in preparing physical documents and supporting documents in accordance with the technical instructions and fulfillment lists that have been made previously. Training through tutorials on how to fill in accreditation forms online provides understanding and skills to the form drafting team on how to use the Sispena-S/M application (School/Madrasah Accreditation Assessment System).